Kesan baja Nitrogen dan kepadatan penanaman ke atas hasil biji Foxtail Millet - Md. Kairudin, Narimah; Mohd Khamin, Nor Masitah (Universiti Putra Malaysia Press, 1995)
The objective of this study was to determine the effects of N fertilizer and plant density on grain yield production of foxtail millet (Setaria italica (Linn.) Beauv.). Four populations of foxtail millet were planted at four plant densities (I, 5, 9 and 17 plant(s)/pot) and supplied with four levels of N jertilizer (0, 50, 100 and 150 kg/ ha), in a completely randomized factorial combination with three replications. The results showed that the four foxtail millet populations had positive response to N fertilizer. Plant density reduced the grain yield production per plant basist. However, the effect of plant density on grain yield/pot varied among the populations.